2013
DOI: 10.3111/13696998.2013.823869
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of atypical long-acting antipsychotics for treating chronic schizophrenia in Finland

Abstract: In Finland, PP-LAI dominated the other LAIs as it was associated with a lower cost and better clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Several health economic models in schizophrenia have been developed [ 28 , 29 , 63 , 64 ], but only one study assessing the cost effectiveness of different antipsychotics in France has been identified [ 30 ]. In 2005, Llorca et al [ 25 ] evaluated the impact in terms of medical benefits and costs of risperidone LAI, haloperidol LAI or oral olanzapine over a 2-year time horizon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several health economic models in schizophrenia have been developed [ 28 , 29 , 63 , 64 ], but only one study assessing the cost effectiveness of different antipsychotics in France has been identified [ 30 ]. In 2005, Llorca et al [ 25 ] evaluated the impact in terms of medical benefits and costs of risperidone LAI, haloperidol LAI or oral olanzapine over a 2-year time horizon.…”
Section: Discussionmentioning
confidence: 99%
“…Six analyses assessing the cost effectiveness of paliperidone LAI have been identified in other countries: Mehnert et al [ 28 ] in Sweden, Zeidler et al [ 29 ] in Germany, Kolek et al [ 64 ] in the Czech Republic, Einarson et al [ 63 ] in Finland, Citrome et al [ 65 ] in the USA and Lee et al in Wales [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was a decision tree comparing the 1-year economic consequence of 3-line antipsychotic treatment sequences. It was selected according to the following reasons: 1) its structure was widely used with eight adaptations [17][18][19][20][21][22][23][24]; 2) it did not consider utility values for the health states other than schizophrenia, such as treatmentrelated side effects; 3) it was a simple model requiring fewer interpretations to replicate the model. Our analysis only compared olanzapine long-acting injection (LAI) with risperidone LAI as a first-line treatment, since this comparison generated non-dominance ICER results in Einarson et al [17].…”
Section: Methodsmentioning
confidence: 99%
“…PP1M is the most cost-effective treatment compared to oral SGAPs or FG-LAIAs ( 47 ). In a study conducted on the basis of Finnish national health data, PP1M treatment was found to be cost-effective in schizophrenia compared to LAI-olanzapine and LAI-risperidone treatments, with a lower hospitalization rate, fewer emergency room admissions and less relapse ( 48 ). PP3M provided advantages in both cost-effectiveness and cost-benefit analyzes, with lower relapses, fewer hospitalizations and fewer emergency room admissions compared to PP1M, LAI-haloperidol, LAI-risperidone and oral olanzapine ( 49 ).…”
Section: Use Of Long Acting Injectable Antipsychotics In Schizophreniamentioning
confidence: 99%